Socioemotional Features and Resilience in Italian University Students with and without Dyslexia - Ghisi, Marta; Bottesi, Gioia; Re, Anna M.; Cerea, Silvia; Mammarella, Irene C. (Frontiers in Psychology, 2016)
Dyslexia is a permanent condition characterized by reading difficulties that include inaccurate or slow and effortful word reading, poor decoding, and poor spelling abilities. People with dyslexia may have psychological and psychopathological issues such as low self-esteem, poor resilience, and symptoms of depression and anxiety. They may also develop social problems and emotional issues, as well as low academic and social self-efficacy. The present study aimed to assess the psychological features of a sample of 28 Italian university students with dyslexia, comparing them with a control group of typically-developing students matched for gender, education, and academic discipline, to enhance our knowledge of dyslexia outcomes in an Italian setting. The results show that university students with dyslexia experience higher levels of somatic complaints, social and attentional problems, lower self-esteem, and higher depression scores than controls, while no difference emerged between the two groups’ resilience scores. In conclusion, the present findings suggest that university students with dyslexia report more psychological issues than students without dyslexia and could benefit from intervention to improve their psychological and physical well-being.